Основні напрями реалізації державної молодіжної політики в Україні: соціально-педагогічний аспект - Корпач, Надія; Korpach, Nadia; Сидорук, Ірина; Sydoruk, Irina (Східноєвропейський національний університет імені Лесі Українки, 2016)
У статті розглядаються поняття «молодіжна політика», «державна молодіжна політика», основні нормативно-законодавчі документи її реалізації, розкриваються основні напрями та пріоритети реалізації державної молодіжної політики в процесі розвитку держави та суспільства. The article discusses the concept of "youth policy", "state youth policy", and the main legislative and regulatory documents for its implementation. The authors reveal the main directions and priorities of state youth policy in the development process of the state and society. In particular: the formation of citizenship, national-Patriotic education of youth); promotion and adoption of healthy and safe lifestyle and health culture among young people; young people acquire the knowledge, skills and other competences outside the education system (development of non-formal education); creation of conditions for youth employment (provide primary and secondary employment and self-employment of youth; creation of conditions for providing housing for young people; provision of partnership support young people living in the temporarily occupied territory of Ukraine and internally displaced persons; the provision of financial support to youth and children's public organizations. The article concluded that the definition of the main principles, directions and mechanisms of realization of youth policy is not a guarantee of its effectiveness. In the formation and implementation of youth policy, active subject must be very young.
The main directions of state youth policy in Ukraine: socio-pedagogical aspect
Keywords: молодь; соціальні проблеми; державна молодіжна політика; young people; social problems; national youth policy